Proceedings 19th IEEE Real-Time Systems Symposium (Cat. No.98CB36279)
DOI: 10.1109/real.1998.739755
|View full text |Cite
|
Sign up to set email alerts
|

Practical solutions for QoS-based resource allocation problems

Abstract: The QoS-based Resource Allocation Model (Q-RAM) proposed in [20] presented an analytical approach for satisfying multiple quality-of-service dimensions in a resource-constrained environment. Using this model, available system resources can be apportioned across multiple applications such that the net utility that accrues to the end-users of those applications is maximized. In this paper, we present several practical solutions to allocation problems that were beyond the limited scope of [20]. First, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
2

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 10 publications
1
87
0
2
Order By: Relevance
“…Rajkumar et al proved that optimal cache partitioning is NPhard [32]. Stone et al proposed an approximation algorithm using convex hulls for solving this problem [38].…”
Section: Background On Cache Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajkumar et al proved that optimal cache partitioning is NPhard [32]. Stone et al proposed an approximation algorithm using convex hulls for solving this problem [38].…”
Section: Background On Cache Partitioningmentioning
confidence: 99%
“…Rajkumar et al prove that optimal cache partitioning is NPhard [32]. Stone et al [38] analytically showed that for minimizing overall miss rate and assuming convex MRC curves, optimal partitioning can be achieved by choosing allocation sizes for which derivatives of miss rates are the same across all workloads.…”
Section: A Partitioning For Performancementioning
confidence: 99%
“…Aura's architecture addresses the problem of representing the adaptation policy that is appropriate to a user's intent using the notion of utility functions -see for instance [22]. Suppose, for example, that a user is viewing a video over a network connection for which the bandwidth suddenly drops.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Our work enables COTS systems to be extended with resource management methods to improve and/or guarantee qualities of service [Rajkumar et al 1998] to individual applications without the need for entire QoS architectures [Abdelzaher and Shin 1998;Rosu et al 1998] to be constructed. As stated above, such execution domains do not suffer from scheduling and context-switching overheads as would be the case for services mapped into traditional process address spaces.…”
Section: Related Workmentioning
confidence: 99%